The Impact of Relationships on Mental Health and Happiness of Aged People - Kaliwal, Asadullah (Journal of Social Sciences - Kabul University, 2023)
This purpose of this retrospective-applicative research is to reveal the effects of the relationships of aged people on their mental health. In this research different articles and academic compo session are analyzed and the research questions are answered. The findings of this study show that relationships have positive effects on the mental health and happiness of the aged people. Connecting with oneself gives them positive feelings and happiness; a connection with the Creator gives them reassurance, prepares them for the afterlife and reduces the anxiety of death. Connecting with nature makes older people feel good and calm, and connecting with other people helps in their happiness and mental health. The findings of the research show that at any level, an elderly citizen has a wide relationship with himself/herself, the creator, nature and people, it benefits his/her mental health.